Options for future ACP-EU trade relations - Solignac Lecomte, Henri-Bernard (ECDPM MaastrichtNL, 1998)
Identifies the major challenges facing ACP countries in terms of their trade policies, as well as ways the EU can support them. Assesses the European Commission proposal to sign free trade agreements between the EU and ACP regions, in relation to its implications for ACP countries. Considers the feasibility of the 'regional' approach as proposed by the EC and presents four options for future ACP-EU trade relations.